Pengaruh Variasi Ketinggian Elektrikal Stik Out Pengelasan Gas Metal Arc Welding (GMAW) Terhadap Sifat Mekanis Pada Pipa Seamless - Imam A Hanifah; Nevada. J. M. Nanulaitta; Graciadiana. I. Huka (Journal Mechanical Engineering, 2023)
Welding is a process of joining two or more metal materials together through a local melting process. There are many types of welding, one of which is Gas Metal Arc Welding (GMAW). In gas metal arc welding (GMAW), one of the factors that affect the result of welding is the height of the stick out. The purpose of this study was to determine the effect of changing the height of the stick out in the gas metal arc welding (GMAW) welding process on the pipe on the mechanical strength of the pipe. The method used in this study is a quantitative method with data collection techniques through the library, and the main data sources obtained directly from the research process, and related interviews regarding the tools and materials used at the Ambon State Polytechnic Mechanical Engineering Laboratory. The results of the research that the author did show that the greatest Impact Strength with a value of 0.1136 KJ/mm2 is at a height of 7 mm electrical stick out and 0.0960 KJ/mm2 is at a height of 9 mm electrical stick out, this can be seen in the figure 4.1 and 4.2 where the graph will have a decreasing trend with increasing variations in the height of the electrical stick out in GMAW welding, while for the bending test the shorter the electrical stick out will result in increased welding penetration, so that the melting of the weld material in the welding process is getting deeper and the cooling process is getting deeper time results in increased ductility of the seamless pipe, it also depends on the thickness of the material being welded, the gas flow rate and metal transfer in the weld. Keywords : GMAW Welding, Stick Out, Mechanical Properties, Seamless Pipe, Impact Test, Bending Test